Analisis Kinerja Rencana Pembangunan Jangka Menengah Daerah (RPJMD) Kabupaten Padang Lawas Utara Tahun 2019-2023 - Siregar, Minta Ito; Adam, Adam; Isnaini, Isnaini (Mahesa Research Center, 2022)
This study aims to analyze the form of evaluating the performance of the North Padang Lawas Regency Regional Medium-Term Development Plan (RPJMD) for 2019-2023 and analyze the inhibiting factors for the 2019-2023 Regional Medium-Term Development Plan (RPJMD) Performance Evaluation of North Padang Lawas Regency. The form of research used in this research is descriptive research with observation data collection techniques, documentation studies and interviews. While the data analysis used is descriptive analysis. The results of this study indicate that the evaluation of the Performance of the Regional Medium-Term Development Plan (RPJMD) of North Padang Lawas Regency for 2019-2023 shows that there are contradictory facts with the maximum efforts that have been made by the North Padang Lawas Regency Bapelitbang in the preparation and control but have not shown maximum results, especially on KPI improvement. Although the term of the RPJMD has not yet expired, every year there are evaluation aspects that can be seen. In other words, there are factors that hinder the implementation of the targets that must be achieved in the North Padang Lawas Regency RPJMD for 2019-2023. Furthermore, there are seven obstacles to the Regional Medium-Term Development Plan (RPJMD) of North Padang Lawas Regency for 2019-2023. These seven obstacles are basically what makes the targets set every year have not been implemented, such as the target in 2019 where North Padang Lawas seeks to implement the concept of building and 2020 with the concept of serving invisible. This can be seen from the KPI, especially the aspects of poverty and stagnant investment development. Then From the six aspects of performance evaluation that Dunn put forward, each aspect still has problems that need to be studied further. This is homework for Bapelitbang North Padang Lawas Regency in meeting the targets and targets of the RPJMD at least until the end of the period in 2023. Suggestions from this research are: the need for regulation socialization and collaboration with every stakeholder interested in strategic design, and it needs to be integrated where Bapelitbang who become the executor of the task need to improve their ability in supervision and control.